The dynamics of linguistic changes in awake craniotomy. A case study - Markiewicz, Piotr (Papers in Linguistics, 2024)
Awake craniotomy (or awake brain surgery) is a technique that allows doctors to safely monitor areas of the brain to remove a tumour or another pathological brain tissue, so as to protect the patient’s linguistic, cognitive, and motor abilities. Such a procedure is considered the gold standard for the resection of brain tissues in functional areas (e.g. linguistic, verbal). The study presents a 23-year-old right-handed man with WHO IV glioblastoma in the left parietal lobe, aphasia and cognitive deficits. The article reports the results of neuropsychological tests in the pre- and postoperative period.